The effects of different ischemic conditioning on strength training recovery - Zihan, Fan; Yanqing, Fu; Ying, Wu (Biology of Sport, 2025)
The aim was to explore the impact of ischemic conditioning (IC) before or after strength training (ST) on recovery and to compare IC with traditional recovery methods (static stretching and foam rolling). Thirty seven healthy males were divided into four groups: CON (no intervention), TRA (stretching and foam rolling after ST), IPC (IC before ST), and PEIC (IC after ST). The ST protocol consisted of five sessions, spaced every two days. Muscle soreness, thigh circumference (TC), countermovement jumps (CMJ), knee isokinetic muscle strength (peak torque [PT], relative peak torque [RPT]), and lactate dehydrogenase (LDH), creatine kinase (CK), malondialdehyde (MDA), superoxide dismutase (SOD), total antioxidant capacity (T-AOC), C-reactive protein (CRP) and interleukin-6 (IL-6) were measured at baseline, 24 h after the first intervention (1 st –24 h), and 24 h and 48 h after the fifth intervention (5 th –24 h, 5 th –48 h). No significant differences were found in CMJ in PEIC at all timepoints ( P > 0.05), while IPC had lower CMJ at 1 st –24 h than baseline ( P < 0.05). Right quadriceps RPT and PT in TRA were unchanged at all timepoints ( P > 0.05), whereas IPC and PEIC had lower values at 1 st –24 h than baseline ( P < 0.05). No significant differences were found in LDH and IL-6 in IPC and PEIC at all timepoints ( P > 0.05), but TRA showed significant differences in LDH at 1 st –24 h and in IL-6 at 1 st –24 h and 5 th –24 h than baseline ( P < 0.05). Results indicated acute PEIC better maintained CMJ than IPC. Acute TRA promoted faster recovery of lower extremity strength than IC, while IC led to a faster recovery of muscle damage and inflammation than TRA.